Drimane Sesquiterpene Alcohols with Activity against Candida Yeast Obtained by Biotransformation with Cladosporium antarcticum - Nicole Cortez; Víctor Marín; Verónica A. Jiménez; Víctor Silva; Oscar Leyton; Jaime R. Cabrera-Pardo; Bernd Schmidt; Matthias Heydenreich; Viviana Burgos; Paola Duran; Cristian Paz (International Journal of Molecular Sciences, 2022)
Fungal biotransformation is an attractive synthetic strategy to produce highly specific compounds with chemical functionality in regions of the carbon skeleton that are not easily activated by conventional organic chemistry methods. In this work, Cladosporium antarcticum isolated from sediments of Glacier Collins in Antarctica was used to obtain novel drimane sesquiterpenoids alcohols with activity against Candida yeast from drimendiol and epidrimendiol. These compounds were produced by the high-yield reduction of polygodial and isotadeonal with NaBH4 in methanol. Cladosporium antarcticum produced two major products from drimendiol, identified as 9α-hydroxydrimendiol (1, 41.4 mg, 19.4% yield) and 3β-hydroxydrimendiol (2, 74.8 mg, 35% yield), whereas the biotransformation of epidrimendiol yielded only one product, 9β-hydroxyepidrimendiol (3, 86.6 mg, 41.6% yield). The products were purified by column chromatography and their structure elucidated by NMR and MS. The antifungal activity of compounds 1–3 was analyzed against Candida albicans, C. krusei and C. parapsilosis, showing that compound 2 has a MIC lower than 15 µg/mL against the three-pathogenic yeast. In silico studies suggest that a possible mechanism of action for the novel compounds is the inhibition of the enzyme lanosterol 14α-demethylase, affecting the ergosterol synthesis.